Colonialismo ambiental, criminalización y resistencias: Las movilizaciones puertorriqueñas por la justicia ambiental en el siglo xxi - José M. Atiles-Osoria (Revista Crítica de Ciências Sociais, 2013)
The struggles for environmental justice have become a fundamental part of Puerto Rican sociopolitical and anticolonial mobilizations since the mid‑twentieth century. In the context of this sociopolitical reality, and placing special emphasis on the criminalization processes used by the U.S. in the post 9/11 era, this article develops three analytical lines: 1) a reflection on environmental colonialism in the context of Puerto Rico; 2) an analysis of the mechanisms of criminalization and repression developed by the governments of the U.S. and Puerto Rico; 3) a review of the Puerto Rican socio‑environmental conflicts between 1999 and 2012. This will allow me to show the close connection between Puerto Rican environmental and anti‑colonial movements, as well as the repressive and criminalization mechanisms deployed against them.